Freckles and solar lentigines have different risk factors in Caucasian women. (28th August 2012) - Ezzedine, K.; Mauger, E.; Latreille, J.; Jdid, R.; Malvy, D.; Gruber, F.; Galan, P.; Hercberg, S.; Tschachler, E.; Guinot, C.
Abstract Background To date, few epidemiological data on the relationships between solar lentigines, freckles and behavioural and constitutional risk factors in Caucasian populations exist. Objectives To investigate the potential impact of behavioural and phenotypic variables, as well as the MC1R genetic background, on the history of facial freckles and the severity of solar lentigines in Caucasian women. Methods The severity of solar lentigines was graded from facial digital images of 523 French middle‐aged women by a dermatologist and summarized by a score afterwards. The history of facial freckles was assessed and the sun‐exposure behaviour was characterized using a six‐category typology. Risk factors including MC1R polymorphism were evaluated using logistic regression models. Results Two constitutive host factors were found to be independently associated with a history of facial freckles: frequent sunburns and the presence of diminished function variants of the MC1R gene. In addition to age, five factors were independently associated with solar lentigines: constitutive host factors (dark skin colour and tanning capacity), a history of freckles, sun‐exposure behaviour and current intake of oral contraceptive or progestogen treatments. Conclusion These results strengthen the hypothesis that solar lentigines are markers of photoaging, whereas freckles are mainly determined by genetic factors. The finding that hormonal treatment is associated with a higher risk for solar lentigines merits further investigations.